INTERNALISASI BUDAYA RELIGIUS OLEH GURU AKIDAH AKHLAK UNTUK MENUMBUHKAN SIKAP AKHLAK MULIA DI MIS BINA DHARMA PARIT RABU - Erwan Erwan; Aslan Aslan; Muhammad Asyura (CV. ADIBA AISHA AMIRA, 2023)
The results of this study indicate that; 1) The process of internalizing religious culture by aqidah morals teachers to foster a noble attitude at MIS Bina Dharma Parit Wednesday class v for the 2022/2023 school year, namely: a) The value transformation stage, at this stage the teacher teaches religious values to foster a noble attitude in the learning process; b) Value Transaction Stage, at this stage the teacher gives examples of religious values to cultivate a noble attitude by applying smiles, greetings, politeness; c) Transinternalization Stage, at this stage the teacher provides habituation and exemplary to cultivate a noble attitude by getting used to time discipline. 2) The application of religious culture by aqidah moral teachers to foster a noble attitude at MIS Bina Dharma Parit Wednesday class v of the academic year, namely: a) The teacher implements a religious program, namely reciting the Koran together before starting learning; b) The teacher provides habituation and example to students to foster a noble attitude by applying smiles, greetings, being polite, and getting used to time discipline behavior. 3) Inhibiting and supporting factors of religious culture to foster a noble attitude at MIS Bina Dharma Parit Wednesday class V for the 2022/2023 academic year. The inhibiting factor is the lack of enthusiasm of students in participating in religious culture programs to foster a noble attitude. While the supporting factors are: a) The readiness of teachers in instilling a religious culture to foster a noble attitude, b) Collaboration between teachers and parents.